Acute brachial plexopathy: an unusual complication from Bee Sting - Hoo, Fan Kee; Hasan, Shariful; Wan Sulaiman, Wan Aliaa; Basri, Hamidon (Professional Medical Publications, 2014)
Brachial plexopathy is usually related to trauma like direct injury to the nerve and stretching injuries. Neurological complications following bee sting are uncommon. Here, we describe a rare case of acute brachial plexopathy as a neurological complication following bee sting. A 23-year-old male initially presented with angioedema and anaphylactic shock one hour after a bee stung at his neck. Twenty four hours after the incidence, he presented with sudden onset of left upper limb weakness. Nerve conduction study and electromyography had shown evidence of left brachial plexopathy.